PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA MENGGUNAKAN ADOBE FLASH CS6 PADA PENGENALAN AKSARA LAMPUNG DI SEKOLAH DASAR - Yulina dan Khusnul Khotimah (Universitas Muhammadiyah Kotabumi, 2018)
This research was a research and development which aimed at developing a learning media based multimedia using adobe flash CS6 applied in Lampung alphabetics material in Elementary school level. This research development consisted of seven stages: (1) indentification of the problem; (2) data collection; (3) product design; (4) design validation; (5) revision; (6) product try out; (7) product revision. This learning media has been validated by those who are expert in the related material and the one who is expert in design and media. Refering to the expert of material and the expert of design and media, it is found that the learning media met the appropriateness standard with grade “very satiesfying” meaning that the media is recommended to be implemented as a learning media at school. The try out was conducted throughout pretest and posttest given to the 1 class of SDN 4 Tanjung Aman consisting of 28 students in order to measure the students’ score before and after the teaching and learning process using this learning media. The data analysis used was normality, homogeneity, and t-test analysis. The result of independent t-test shows that the significant value (0,00) is less than the value of (0,05). Therefore, it reveals that the use of learning media based multimedia using Adobe flash CS6 is appropriate to be used in teaching Lampung alphabetics material.